Mind the Gap: Continuity of Care in Student-Run Free Clinics - Lee, David; Quach, Kaitlyn; Abolarin, Zabrina; Wang, Josephine (Journal of Student-Run Clinics, 2024)
Background: Patient continuity of care is closely tied with patient health outcomes, encompassing both consistent access to health service points and patient-professional relationships. However, insurance status often limits a patient’s ability to maintain continuity of care. Student-run free clinics aim to address this gap, initially focusing on primary care service lines and now diversifying into multi-disciplinary operations. Ongoing evaluation and new collaborations and resources likely will be necessary for student-run free clinics to manage the growing magnitude and breadth of patient needs. Purpose: To apply the insights shared at the Society of Student-Run Free Clinics 2023 Annual Meeting’s Bridge-the-Gap session, which aims to address challenges in patient continuity of care, toward synthesizing generalizable strategies. These strategies will help student-run free clinics develop actionable approaches to strengthen patient continuity of care. Summary: Three themes emerged over the course of multi-disciplinary discussion: 1) consistency of healthcare services, 2) breadth of healthcare service lines, and 3) mobility and portability of healthcare resources. Additional research toward developing programs and resources to strengthen patient continuity of care should be conducted to enable student-run free clinics to provide their patients with world-class care and a medical home. This editorial explores areas where student-run clinics can improve patient care via increasing opportunities for continuity of care.